2017
DOI: 10.1103/physrevc.95.044328
|View full text |Cite
|
Sign up to set email alerts
|

Inversion doublets of reflection-asymmetric clustering in Si28 and their isoscalar monopole and dipole transitions

Abstract: Background: Various cluster states of astrophysical interest are expected to exist in the excited states of 28 Si. However, they have not been identified firmly, because of the experimental and theoretical difficulties. Purpose: To establish the 24 Mg + α, 16 O + 12 C, and 20 Ne + 2α cluster bands, we theoretically search for the negative-parity cluster bands that are paired with the positive-parity bands to constitute the inversion doublets. We also offer the isoscalar monopole and dipole transitions as a pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…by the softness of these nuclei and related shape coexistence [4]. The low-energy isoscalar monopole (IS0) and dipole (IS1) states in light nuclei can serve as fingerprints of clustering [5,6] one of the basic features of light nuclei. IS1 states can also deliver important information on some mean-field features, such as vorticity [7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
“…by the softness of these nuclei and related shape coexistence [4]. The low-energy isoscalar monopole (IS0) and dipole (IS1) states in light nuclei can serve as fingerprints of clustering [5,6] one of the basic features of light nuclei. IS1 states can also deliver important information on some mean-field features, such as vorticity [7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
“…In addition, we have also calculated the continuum strength of the isoscalar dipole (IS1) transition for the α + 40 Ca system, which has been proposed as a effective probe for the asymmetric cluster system [9]. The matrix element of the IS1 transition is prominently increased in the low excitation region, and this result is similar to the result in the IS0 transition.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…The continuum strength function for the transition from the ground state to the unbound continua, which is induced by the external field, is calculated from the ABC calculation [14]. As for the operator of the external field, we consider the monopole (λ = 0) and dipole (λ = 1) operators, which are basically written in the nucleon degree of freedom like [8,9]…”
Section: Macroscopic α Cluster Model In 44 Ti and Te Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the isoscalar monopole/dipole transitions attract much interest as they may overcome this difficulty. It was shown that these transitions strongly populate the cluster resonances and enable us to investigate their properties [1][2][3][4]6]. As an example of such cases, we have theoretically investigated the cluster resonances in 20 Ne, 44 Ti [4] and 24 Mg [5], which I report in this contribution.…”
Section: Introductionmentioning
confidence: 99%